Rad25p, a DNA helicase subunit of yeast transcription factor TFIIH, is required for promoter escape in vivo. - Ostapenko, D; Gileadi, O (2000)
The general transcription factor TFIIH is required for initial DNA unwinding and promoter escape by RNA polymerase II in vitro. We examined whether Rad25p, a DNA helicase subunit of TFIIH, mediates promoter opening and promoter escape in the yeast Saccharomyces cerevisiae. DNA unwinding was probed with an in vivo permanganate reactivity assay, in a temperature-sensitive mutant of RAD25. The consequences of Rad25p inactivation were promoter-specific. Whereas in the TDH2 promoter permanganate reactivity was entirely abolished, the reactivity at the GAL1 and GAL10 promoter regions was only moderately affected. In the GAL genes permanganate reactivity uniformly decreased downstream of the transcription start site, indicating that progression of RNA polymerase II to this region was impaired. Our results suggest that in yeast cells, promoter opening is not sufficient for productive initiation and that Rad25p-mediated promoter escape may be a limiting step in the transcription of some promoters.